2014
DOI: 10.1016/j.nano.2013.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanodiamond–daunorubicin conjugates to overcome multidrug chemoresistance in leukemia

Abstract: Nanodiamonds (NDs) are promising candidates in nanomedicine, demonstrating significant potential as gene/drug delivery platforms for cancer therapy. We have synthesized ND vectors capable of chemotherapeutic loading and delivery with applications towards chemoresistant leukemia. The loading of Daunorubicin (DNR) onto NDs was optimized by adjusting reaction parameters such as acidity and concentration. The resulting conjugate, a novel therapeutic payload for NDs, was characterized extensively for size, surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 51 publications
2
63
0
1
Order By: Relevance
“…[5][6][7] In particular, the successful use of DNDs in cancer treatment has greatly captured the attention of the scientific community. [8][9][10][11] Although numerous plant compounds have been widely studied for their antitumor activities, [12][13][14][15] to date only three papers describe the coupling of natural secondary metabolites with DNDs aimed at enhancing their bioavailability and bioactivity. The first of them illustrated the antimicrobial activity of menthol ((1R,2S,5R)-2-isopropyl-5-methylcyclohexanol)-modified ND particles.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] In particular, the successful use of DNDs in cancer treatment has greatly captured the attention of the scientific community. [8][9][10][11] Although numerous plant compounds have been widely studied for their antitumor activities, [12][13][14][15] to date only three papers describe the coupling of natural secondary metabolites with DNDs aimed at enhancing their bioavailability and bioactivity. The first of them illustrated the antimicrobial activity of menthol ((1R,2S,5R)-2-isopropyl-5-methylcyclohexanol)-modified ND particles.…”
Section: Introductionmentioning
confidence: 99%
“…Although researchers now have a greatly expanded set of knobs to turn when designing NPs, it is generally not clear how a change to a specific vehicle feature will alter the effectiveness of a drug, and hence design of novel drug carriers requires extensive and costly parametric studies that are generally specific to the system upon which the experiments were performed. Theoretical and computational modelling of the delivery process can greatly reduce the need for physical experiments and provide general design principles to expedite the design process [4][5][6][7][8][9].…”
Section: Overviewmentioning
confidence: 99%
“…Nanodiamonds (NDs) is a class of nano particles that has already shown both the delivery and the enhanced function of its payload (17). Man and coworkers investigated a novel therapeutic payload (18). NDs were developed such that daunorubicin (DNR) could be reversibly bound and released.…”
Section: Nanodiamons-daunorubicin and Multidrug Resistance In Leukemiamentioning
confidence: 99%
“…With this, they demonstrated the potential to improve cancer treatment in particular regarding resistant strains. Man and coworkers (18) suggested that with the introduction of a gene therapy component, the expression of the proteins causing MDR might be actively reduced. NDs have already been investigated and showed excellent biocompatibility in vitro.…”
Section: Nanodiamons-daunorubicin and Multidrug Resistance In Leukemiamentioning
confidence: 99%